Pengaruh Penerapan Model Pembelajaran Collaborative Problem Solving Terhadap Peningkatan Kemampuan Koneksi Matematis pada Siswa SMP - Andri Herdian; Mumun Syaban; Puji Budilestari (EDUCARE, 2015)
Mathematical connection capability is one of the goals of learning mathematics in schools contained in the curriculum guide. However, the current state of mathematics learning in schools still shows the students' low mathematical connection abilities. For this reason, learning is needed that is able to provide opportunities for students to develop mathematical connection skills. One of the lessons that can be used is the Collaborative problem solving learning model. This learning model has 4 specific steps in its implementation. This study aims to determine whether there is an increase in students 'mathematical connection skills using Collaborative problem solving learning models and find out whether the increase in students' mathematical connection skills with Collaborative problem solving learning models is better than students who use conventional learning. This research is a quasi-experimental study with group design. The results of the study show that learning mathematics using the Collaborative problem solving model can improve mathematical connection skills in middle school students. Mathematical learning with a collaborative problem solving learning model is significantly better in increasing the ability of mathematical connections in junior high school students compared to students who take conventional learning in terms of maematic connection skills in middle school students.